Essentially derived variety concept in plant variety rights protection system: underlying economic theories, and issues in implementation - P A Lakshmi Prasanna; L V Subba Rao; A S Hari Prasad; Amtul Waris; S Arun Kumar (Agricultural Economics Research Review, 2023)
Under Trade Related Aspects of Intellectual Property Rights (TRIPS) agreement, World Trade Organization member-countries are mandated to create Intellectual Property Rights (IPR) system for plant varieties. Keeping in view specificities of plant breeding sector, “tailored” IPR system of Plant variety rights/ Plant Breeders’ Right system was developed. The concept of Essentially Derived Variety (EDV) was introduced into plant variety protection system through 1991 UPOV convention. In this backdrop, in the current study an attempt has been made to trace theories underlying, and rationale behind EDV concept by reviewing economic models of innovation. The study documented some challenges in implementation of EDV concept and also examined EDV status in India and future prospects.